Czy wszyscy znają Jasia i Małgosię? Problem kanonu baśniowego na przykładzie baśni ze zbioru Kinder- und Hausmärchen Wilhelma i Jakuba Grimmów - Kowalczyk, Kamila Aleksandra (Er(r)go. Teoria - Literatura - Kultura, 2017)
[for abstract in Polish scroll down] Kamila Kowalczyk Institute of Polish Faculty of Philology University of Wrocław Poland Is Everyone Familiar with Hansel and Gretel? The Issue of Fairy Tale Canon on the Example of the Fairy Tales from the Kinder- und Hausmärchen Collection by Jacob and Wilhelm Grimm Abstract: The article considers the problems connected with the idea of fairy tale canon, with attention to the fairy tales from the Kinder- und Hausmärchen (Children’s and Household Tales) collection by Jacob and Wilhelm Grimm. Instead of a primary fairy tale or canonical fairy tale, the author proposes a concept of a fairy tale module – an imaginary structure consisting of multiple versions of a single fairy tale which functions in various registers of production and reception (traditional culture, written culture, technological culture). The article also contains a discussion of the fairy tale re-narration based on the contemporary texts of culture which modify those fairy tales and which are well-rooted in collective imagination. The fairy tales basically work as constructs whose shape is determined by other texts of culture and various media (literature, film, comic books, etc.). The article also notes the economic dimension of Grimm’s fairy tales which have been present in culture for over 200 years and which still remain subject to constant changes – the fact particularly apparent in the area of popular culture. Keywords: cultural theory, literary theory, fairy-tale theory, genology. postmodernity Abstrakt: W artykule podjęto rozważania na temat problemów związanych z pojęciem kanonu baśniowego ze szczególnym uwzględnieniem baśni ze zbioru Wilhelma i Jakuba Grimmów Kinder- und Hausmärchen. Celem tekstu jest przedstawienie propozycji badawczej, która na miejsce baśni pierwotnej czy też baśni kanonicznej proponuje pojęcie wzorca baśniowego – struktury wyobrażeniowej ukształtowanej na podstawie różnych wersji jednej baśni, funkcjonującej w różnych rejestrach nadawczych i odbiorczych (kultura tradycyjna, kultura pisma, kultura technologiczna). Ponadto, w artykule znajduje się omówienie zjawiska baśniowej renarracji na podstawie współczesnych tekstów kultury, które modyfikują doskonale zakorzenione w masowej wyobraźni baśnie. Baśnie funkcjonują przede wszystkim jako konstrukty, na których kształt mają wpływ również inne teksty kultury i różne kanały ich przyswajania (literatura, film, komiks, itd.). W pracy zwrócono również problem na wymiar ekonomiczny baśni Grimmowskich, które obecne są w kulturze już od ponad 200 lat i podlegają ciągłym transformacjom, co szczególnie jest zauważalne w przestrzeni kultury popularnej. Słowa klucze: teoria kultury, teoria literatury, teoria baśni, postmodernizm, genologia